2005
DOI: 10.1093/deafed/enj018
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Word Learning in a Hearing Child of Deaf Adults

Abstract: It is unclear how children develop the ability to learn words incidentally (i.e., without direct instruction or numerous exposures). This investigation examined the early achievement of this skill by longitudinally tracking the expressive vocabulary and incidental word-learning capacities of a hearing child of Deaf adults who was natively learning American Sign Language (ASL) and spoken English. Despite receiving only 20% of language input in spoken English, the child's expressive vocabularies at 16 and 20 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
1
15
0
3
Order By: Relevance
“…Their receptive vocabulary is comparable to monolingual peers, as already shown in previous studies (Brackenbury, Ryan, and Messenheimer 2005;Grüner 2004;Schiff and Ventry 1976). However, they reach lower test scores in expressive language tests than monolingual peers, especially in the production of verbs and prepositions and in the classification of nouns; findings that have also been documented in other studies (Brackenbury, Ryan, and Messenheimer 2005;Capirci et al 2002;Griffith 1985;Schiff and Ventry 1976). Some codas in our study perform particularly worse on grammatical subtests (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Their receptive vocabulary is comparable to monolingual peers, as already shown in previous studies (Brackenbury, Ryan, and Messenheimer 2005;Grüner 2004;Schiff and Ventry 1976). However, they reach lower test scores in expressive language tests than monolingual peers, especially in the production of verbs and prepositions and in the classification of nouns; findings that have also been documented in other studies (Brackenbury, Ryan, and Messenheimer 2005;Capirci et al 2002;Griffith 1985;Schiff and Ventry 1976). Some codas in our study perform particularly worse on grammatical subtests (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Codas produce their first spoken words between the age of 11 (Capirci et al 2002) and 18 months (Griffith 1985). They develop their early vocabulary similar to monolingual children (Brackenbury, Ryan, and Messenheimer 2005) and reach average to above average scores in a standardised vocabulary test (Daniels 1993).…”
Section: Spoken Language Acquisition In Codasmentioning
confidence: 97%
See 1 more Smart Citation
“…That is, when children produce a manual tact they should be able to respond as ''listeners'' to the visual and kinesthetic products of that response, in much the same way as they respond as listeners to the auditory stimuli they produce during vocal naming. In support of this claim, it has been shown that deaf children who learn signing, and hearing children who learn spoken languages from birth, both reach all the conventional linguistic milestones at the same rate (e.g., Brackenbury, Ryan, & Messenheimer, 2006;Genesee, 1987;Pettito, 1987Pettito, , 1988Pettito, , 1993Pettito & Marentette, 1991). Pettito (1993) concludes that humans can acquire language in either spoken or manual-sign modalities but if the child is exposed only to one language environment (e.g., spoken) this becomes the main modality while the other unused modality subsequently serves a secondary signaling or augmentative function (and see Acredolo & Goodwin, 1990).…”
mentioning
confidence: 90%
“…One possible explanation is that children with typical hearing usually learn a large part of their vocabularies incidentally (Nagy, McClure, & Mir, 1997;Saffran, Newport, Aslin, & Tunick, 1997). While children of parents who are DHH and use American Sign Language acquire signed language vocabulary incidentally (Brackenbury, Ryan, & Messenheimer, 2006), most children who are DHH require explicit instruction to improve their vocabulary performance (Lederberg & Spencer, 2008;Paatsch, Blamey, Sarant, & Bow, 2006). Hearing loss in and of itself does not preclude the development of vocabulary, but it does impose constraints that educators must help students overcome.…”
Section: Discussionmentioning
confidence: 99%